Assessing the Impact of Microfinance on the Income Level of Small-Scale Farmers - Bhandari, Bishnu Prasad (Janapriya Journal of Interdisciplinary Studies, 2024)
The study analyzes the impact of microfinance in terms of income level of small-scale farmers due to involvement in microfinance. The impact has been observed in rural and urban settings of Nepal. Rural and urban areas are assumed according to the promulgation of the new constitution in 2015, where local administrative units were restructured into 753 local units. The sampling strategy involved in the research was multiple stages: district selection through purposive sampling, local unit selection through lottery sampling, and respondent selection through snowball sampling. Impact has been measured by employing paired sample t-test, revealing statistically significant increases in household income post-intervention (p=0.001) for both rural and urban households The findings indicate a notable shift in income distribution, with a higher percentage of households transitioning into higher income brackets, especially those earning above 5 Lakhs. In rural areas, 25.2% of households moved to the higher income category after joining MFIs, compared to 11.3% before. Similarly, 26.7% of urban households shifted to this higher income bracket after joining MFIs. Therefore, the overall findings suggest that MFIs play a crucial role in enhancing household income, particularly by facilitating upward income mobility for small-scale farmers. In rural, urban and overall cases, the paired sample t-test shows a significant increase in household income after joining MFIs. Therefore, joining MFIs seems to positively impact household income levels in both rural and urban areas.